2005
DOI: 10.1094/fg-2005-0831-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization Impacts on Stand and Forage Mass of Cool-Season Grass-Legume Pastures

Abstract: Combining the benefits of legume N2fixation and N fertilization may increase the productivity and profitability of pasture systems. Our objectives were to study the effects of N fertilization on productivity and persistence of legumes in mixtures with cool‐season grasses under rotational stocking with short grazing periods. Twelve N fertilization regimes ranging from 0 to 336 kg of N per ha were applied annually to smooth bromegrass and reed canarygrass in monoculture and mixture with alfalfa, birdsfoot trefoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The high clover:grass ratios observed in the spring of the fifth post‐seeding year for all KC‐grass mixtures could potentially be problematic for grazing animals, KC having the potential to cause bloat (10,15). Such results are in accordance with previous studies, which also reported a gradual increase in KC contribution to total forage yield, and a propensity for KC to dominate swards several years after seeding (1,2,6,16). The present study suggests that KBG should not be seeded with KC in southwestern Québec, since it does not have the ability to sufficiently contribute to yield in proportions (i.e., at least 50%) that would limit bloat potential (4).…”
Section: Kura Cloversupporting
confidence: 93%
See 1 more Smart Citation
“…The high clover:grass ratios observed in the spring of the fifth post‐seeding year for all KC‐grass mixtures could potentially be problematic for grazing animals, KC having the potential to cause bloat (10,15). Such results are in accordance with previous studies, which also reported a gradual increase in KC contribution to total forage yield, and a propensity for KC to dominate swards several years after seeding (1,2,6,16). The present study suggests that KBG should not be seeded with KC in southwestern Québec, since it does not have the ability to sufficiently contribute to yield in proportions (i.e., at least 50%) that would limit bloat potential (4).…”
Section: Kura Cloversupporting
confidence: 93%
“…Despite its great potential, KC use remains marginal mainly due to a characteristic slow development (3,5,6,13,14). Kura clover's contribution to yield is initially minimal; it however gradually increases in post-seeding years (1,2,5,6). If KC's development pattern is well known, there is however limited information on how KC yield contribution over time may differ when seeded with various grass species.…”
Section: Introductionmentioning
confidence: 99%
“…Cuomo et al. (2005) observed that persistence of alfalfa ( Medicago sativa L.) and birdfoot trefoil ( Lotus corniculatus L.) was not affected by the application of 56 kg N ha −1 when overseeded into reed canarygrass ( Phalaris arundinacea L.), but the N increased grass forage accumulation and nutritive value.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies reported a negative effect of N fertilization on overseeded legumes (Mulder, 1952;Robinson & Sprague, 1947), studies with cool-season species demonstrated that low N fertilization levels may stimulate grass growth without impacting legume performance. Cuomo et al (2005) observed that persistence of alfalfa (Medicago sativa L.) and birdfoot trefoil (Lotus corniculatus L.) was not affected by the application of 56 kg N ha −1 when overseeded into reed canarygrass (Phalaris arundinacea L.), but the N increased grass forage accumulation and nutritive value.…”
Section: Forage Measurementsmentioning
confidence: 99%
“…Previous research has shown legume tolerance to N applications up to 150 kg N ha −1 (Gardner et al., 1960; Mackenzie & Daly, 1982; Hoveland et al., 1995; Harris & Clark, 1996; Cuomo et al., 2005). Nitrogen application up to 112 kg N ha −1 did not suppress ladino clover in orchardgrass ( Dactylis glomerata L.) when applied as split applications across the growing season (Nelson & Robins, 1957).…”
Section: Introductionmentioning
confidence: 99%